IMPROVING METHODS OF ACCOUNTING COSTS AND PRODUCT COSTS IN CONDITIONS OF TRANSFORMATION OF INTERNAL AUDIT TO INTERNATIONAL AUDITING STANDARDS - Mardanov Muzaffar Kholboevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article explores the possibilities of introducing international standards and methods in the context of organizing an internal audit of costs and the cost of products, works and services provided at transport enterprises.